Analysis of Heterotic Potential for Earliness, Yield and its Attributing Traits in Okra (Abelmoschus esculentus L. Moench) - Patel, D. D.; Delvadiya, I. R.; Kumar, Rajneesh (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted during the late kharif season (July to November, 2023) at the Genetics and Plant Breeding Research Farm, School of Agriculture, Lovely Professional University, Phagwara, Punjab India. This study assessed heterosis in okra (Abelmoschus esculentus L.) for 12 traits, including earliness and fruit yield using Randomized Block Design. Thirty-five F1s were obtained from crossing 7 lines with 5 testers in line×tester method and compared with one commercial check (Punjab-8) to estimate standard heterosis and heterobeltiosis among better parents. Significance of mean square due to genotypes revealed the presence of considerable genetic variability among the material studies for almost all the traits. The best positive heterotic cross over better parent (Heterobeltiosis) and standard check (Punjab 8) for fruit yield plant-1 was Go-6×Arka Abhay (72.32%) and Phule Prajatiti×Arka Abhay (41.63%) respectively. While Punjab Suhanani×GAO-5 (-12.05%) was found as negatively heterotic cross for days to 50% flowering over better parent and GAO-8×Arka Abhay (-13.26%) over standard check respectively. For days to first picking Pusa Savani×VRO-106 (-14.44%) exhibited negatively significant heterosis over better parent and Phule Prajatiti×Arka Abhay (-14.49%) over standard check respectively, that are important to exploit the earliness traits in okra. The hybrid Phule Prajatiti×Arka Abhay, which has a high potential for yield and fruits can be picked earlier which may evaluated further for early kharif season in Punjab.